(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the article discusses the issue of preparing students to ensure a safe learning environment in educational institutions. Various strategies, methods and challenges faced by educational institutions in creating a culture of safety among students were also discussed. The article examines modern approaches to safety education, including active modeling, the use of simulation exercises, technology integration, and individual student characteristics. Issues such as cultural differences, lack of safety awareness, and the need for continually updated training strategies are explored.